2014
DOI: 10.1038/bjc.2014.250
|View full text |Cite
|
Sign up to set email alerts
|

AEG-1 expression is an independent prognostic factor in rectal cancer patients with preoperative radiotherapy: a study in a Swedish clinical trial

Abstract: Background:Preoperative radiotherapy (RT) is widely used to downstage rectal tumours, but the rate of recurrence varies significantly. Therefore, new biomarkers are needed for better treatment and prognosis. It has been shown that astrocyte elevated gene-1 (AEG-1) is a key mediator of migration, invasion, and treatment resistance. Our aim was to analyse the AEG-1 expression in relation to RT in rectal cancer patients and to test its radiosensitising properties.Methods:The AEG-1 expression was examined by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…The proportion of positively stained cells and the staining intensity were higher in tumour tissues than in adjacent normal lung tissues. Our results are consistent with earlier studies, in that AEG-1 is over-expressed in many types of carcinomas, such as breast cancer, 7 prostate cancer, 9 cervical cancer 11 and hepatocellular carcinoma, 14 among others.…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of positively stained cells and the staining intensity were higher in tumour tissues than in adjacent normal lung tissues. Our results are consistent with earlier studies, in that AEG-1 is over-expressed in many types of carcinomas, such as breast cancer, 7 prostate cancer, 9 cervical cancer 11 and hepatocellular carcinoma, 14 among others.…”
Section: Discussionsupporting
confidence: 93%
“…AEG-1 plays crucial roles in tumor progression such as transformation, survival, invasion, metastasis, angiogenesis and drug resistance in various types of human cancers (22)(23)(24)(25)(26)(27)(28). Furthermore, recent reports have revealed that AEG-1 participates in the regulation of the EMT process under diverse cellular conditions (29)(30)(31)(32)(33)(34)(35).…”
Section: Aeg-1 Promotes Mesenchymal Transition Through the Activationmentioning
confidence: 99%
“…We speculate that the increased distant recurrence rate after radiation in high AEG-1 expressing tumors could be due to the metastasis promoting properties of AEG-1 [13]. AEG-1, also known as Metadherin (MTDH) and LYRIC, was originally identified as a human immunodeficiency virus-1 - inducible gene in human fetal astrocytes [14].…”
Section: Introductionmentioning
confidence: 99%